2022
DOI: 10.1029/2021av000542
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 Economic Downturn on Tropospheric Ozone Trends: An Uncertainty Weighted Data Synthesis for Quantifying Regional Anomalies Above Western North America and Europe

Abstract: Tropospheric ozone is a greenhouse gas that contributes to climate change, and an air pollutant detrimental to human health and agriculture (Fleming et al., 2018;Gaudel et al., 2018;Mills et al., 2018). The tropospheric ozone burden is largely maintained by photochemical ozone production involving precursor gases, such as nitrogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 90 publications
0
29
0
Order By: Relevance
“…Indeed, several studies have looked at O 3 changes early in 2020 and found little change (Bekbulat et al, 2021) or even an increase (Zhao et al, 2020), likely due to reduced NO x suppression in winter or early spring conditions. Some studies have identified small reductions in free tropospheric O 3 concentrations over the Northern Hemisphere (Chang et al, 2022;Steinbrecht et al, 2021), which reverses the earlier trends (Gaudel et al, 2020). Campbell et al (2021) used the NOAA forecasting system and observations to examine 2020 changes and found a complex pattern of increases and decreases, depending on location and time of year.…”
mentioning
confidence: 99%
“…Indeed, several studies have looked at O 3 changes early in 2020 and found little change (Bekbulat et al, 2021) or even an increase (Zhao et al, 2020), likely due to reduced NO x suppression in winter or early spring conditions. Some studies have identified small reductions in free tropospheric O 3 concentrations over the Northern Hemisphere (Chang et al, 2022;Steinbrecht et al, 2021), which reverses the earlier trends (Gaudel et al, 2020). Campbell et al (2021) used the NOAA forecasting system and observations to examine 2020 changes and found a complex pattern of increases and decreases, depending on location and time of year.…”
mentioning
confidence: 99%
“…The rationale of data fusion developed in Chang et al. (2022) can be summarized by the following statistical structure: various0.25emdata0.25emsources=fusedconsensusprocess+discrepancyfromindividualdataset+randomnoise $\text{various}\,\text{data}\,\text{sources}=\text{fused}\,\text{consensus}\,\text{process}+\text{discrepancy}\,\text{from}\,\text{individual}\,\text{dataset}+\text{random}\,\text{noise}$ …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Stauffer et al (2022) recently examined the stability of global ozonesonde network and concluded that those data are suitable to study trends (albeit the accuracy depends on the sampling frequency in each station), but trends at the individual station would much likely reflect localized variability (and partial regional variability). Therefore it is important to consider all available data sources as a whole for better characterizing large-scale variability (Chang et al, 2022;Cooper et al, 2010;Stauffer et al, 2022). Even though spatial heterogeneity is not fully accounted for in our current methodology, we evaluated the sensitivity of our data fusion method to spatial heterogeneity by also calculating the free-tropospheric ozone trends using a geographically weighted modeling approach.…”
Section: Data Fusion Of Free Tropospheric Measurements From Multiple ...mentioning
confidence: 99%
See 1 more Smart Citation
“…(Borhani & Noorpoor, 2017 , 2020 ; Borhani et al, 2016 a, 2017 b, 2019 , 2023 ; Cheraghi & Borhani, 2016a , 2016b ; Hoveidi et al, 2017 ; Maddah et al, 2022 ; Mazzeo et al, 2005 ; Motesaddi Zarandi et al, 2015 ). Ozone concentrations are usually measured using ground-based and satellite systems (Chang et al, 2022 ; Massagué et al, 2022 ; Reshi et al, 2022 ; Wang et al, 2021 ). For example, Borhani et al ( 2022c ) investigated the changes in tropospheric ozone and its relation to ozone precursors (i.e., CO, NO 2 , and NO) and meteorological conditions observed at 22 ground-based stations of the Air Quality Control Company (AQCC) in Tehran from 2001 to 2020.…”
Section: Introductionmentioning
confidence: 99%